ON THE WAY TO ENTERING THE WORLD EDUCATIONAL AND SCIENTIFIC SPACE - E. V. Nuzhdaeva (Высшее образование в России)
This article presents the current state ofuniversity international cooperation, discusses the issues concerning internationalization of education, formulates the main problems of cooperation with foreign partners and suggests options for their solution. Among the main challenges Chuvash State University faces today is the formation of a unique university's brand, integration into international education and research market, promotion of the research results and findings to the world scientific community.